10-year risk for cardiovascular diseases according to the WHO prediction chart: findings from the National Health and Morbidity Survey (NHMS) 2019 - Halizah Mat Rifin; Mohd Azahadi Omar; Kim Sui Wan; Wan Shakira Rodzlan Hasani (BMC, 2024)
Abstract Background There has been a significant increase in the incidence of cardiovascular disease (CVD) in Malaysia. It is important to identify the group at high risk of CVD. This study aimed to assess the population distribution and factors associated with 10-year CVD risk among adults aged 40 to 74 years in Malaysia. Methods This study used secondary data from the NHMS 2019, a nationally representative cross-sectional population study. The following measurements were collected: anthropometric, systolic blood pressure, fasting blood glucose, total cholesterol, smoking, and sociodemographic. The 2019 WHO Southeast Asia laboratory-based charts were used to estimate individuals' CVD risk. These charts predict significant cardiovascular events over ten years. Multiple logistic regression analysis was employed to ascertain the factors that are linked to elevated or extremely elevated risk of CVD. Results A total of 5,503 respondents were included in the analysis. Less than one-quarter of the respondents were current smokers and obese. Approximately 41.7%, 30.9%, and 22.5% of the participants had extremely low risk (less than 5%), low risk (between 5% and less than 10%), and moderate risk (between 10% and less than 20%), respectively. A total of 4.9% of the participants were categorised as having high (20% to < 30%) or very high (CVD) risk (≥ 30%). This classification was more prevalent among males (7.3%) than among females (2.5%; p < 0.001). The factors associated with high/very high CVD risk were unemployment (aOR = 1.88, 95% CI = 1.47-2.40), those with non-formal and primary education level (aOR = 2.36, 95% CI = 1.36 − 4.12 and aOR = 3.28, 95% CI = 2.10 − 5.12, respectively), and being physically inactive with obesity (aOR = 2.19, 95% CI = 1.18 − 4.08). Conclusions This study revealed that almost 5% of the population in Malaysia has a high 10-year CVD risk. These findings highlight Malaysia's urgent need for comprehensive CVD prevention efforts.